2021
DOI: 10.1111/jce.15297
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptance of subcutaneous versus transvenous defibrillator systems: A multi‐center experience

Abstract: Background: The subcutaneous implantable cardioverter-defibrillator (S-ICD) is an effective alternative to the transvenous ICD. No study has yet compared S-ICD and transvenous ICD by assessing patient acceptance as a patient-centered outcome.Objective: To evaluate the patient acceptance of the S-ICD and to investigate its association with clinical and implantation variables. In patients with symptomatic heart failure and reduced ejection fraction (HFrEF), the acceptance of the S-ICD was compared with a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…8 Patient acceptance scores of the EV ICD patients were statistically significantly better than those reported by S-ICD and TV-ICD patients using historical norms. 4 Subscale comparisons indicated that EV ICD patients reported less device-related distress and less body image concerns than patients with S-ICD and TV-ICDs. Moreover, the EV ICD patients reported more positive appraisal of the ICD than TV-ICD patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 Patient acceptance scores of the EV ICD patients were statistically significantly better than those reported by S-ICD and TV-ICD patients using historical norms. 4 Subscale comparisons indicated that EV ICD patients reported less device-related distress and less body image concerns than patients with S-ICD and TV-ICDs. Moreover, the EV ICD patients reported more positive appraisal of the ICD than TV-ICD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, a retrospective comparison to historical data from a previous study 4 that included FPAS survey results for patients with S‐ICD and TV‐ICD systems was performed by extracting data points from the published dot plots.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we have recently demonstrated positive patient acceptance of the S-ICD, even in groups at risk of psychological distress, such as females or those with a smaller body habitus, independent of the generator positioning. 22 Patients with inherited cardiac arrhythmias and cardiomyopathies are usually younger and could be considered suitable for S-ICD therapy. Nevertheless, data from the literature in these scenarios are still scarce and debatable.…”
Section: Tv-icd Study or Subgroupmentioning
confidence: 99%
“…5 Moreover, it must be recognised that, despite the initial concern about the size of the current S-ICD, patient acceptance is positive and its use is sometimes associated with better positive appraisal in comparison with the TV-ICD. 22…”
Section: Tv-icd Study or Subgroupmentioning
confidence: 99%
“…In contrast, previous reviews with subcutaneous ICDs (S-ICD) in pediatric populations 4 has suggested only minor implant modifications may need to be considered, and Vincentini et al did not find any differences in device acceptance by body habitus. 5 The size of the EV-ICD may also be a consideration for shared decision making with respect to the decision of which ICD to implant in which patient. Specifically, the EV-ICD compares favorably in size…”
mentioning
confidence: 99%